Predicting Muslim medical tourists' satisfaction with Malaysian Islamic friendly hospitals - Zailani, S.; Ali, S.M.; Iranmanesh, M.; Moghavvemi, S.; Musa, G. (Elsevier, 2016)
This paper examines the factors affecting the Muslim medical tourists' satisfaction, and the role of their attitudes in shaping their clinical experience based on the expectation-disconfirmation paradigm. Data from a survey of 243 Muslim medical tourists who had received treatment from Malaysian Islamic friendly hospitals were analysed using the partial least squares technique. The findings provide evidence that Muslim medical tourists' satisfaction is dependent on the doctors' and hospitals' roles; whilst, the nurse's halal practice is not associated with it. The study also demonstrates that Muslim medical tourists' attitudes only play a mediator role between the hospital's halal practice and Muslim medical tourists' satisfaction. The research result provides useful information in understanding the critical halal practices and, more particularly, aims at helping Islamic hospitals offer quality healthcare services that suit the Muslim medical tourists' needs and, consequently, attracts the Islamic medical tourists.